Eine Provokation und ihre Folgen. Zum “deutschen Trauerspiel” «Die Plebejer proben den Aufstand» von Günter Grass: [A Provocation and its Consequences. On the “German Tragic Drama” «The Plebeians Rehearse the Uprising» by Günter Grass] (Studia theodisca, 2017)
Die Plebejer proben den Aufstand. Ein deutsches Trauerspiel (1966) by Günter Grass aroused great scandal, because the play denounces the tactics of Bertolt Brecht with regard to the workers’ uprising in East Germany on June 17, 1953. However, Grass always relativized this and claimed to have shown the problematic relationship between artist and politics in general. The present contribution argues that Grass actually attacked frontally none other than Brecht and that he exploited the debate in the leftist student magazine konkret, the West-German mouthpiece of the 1968 revolt.